САМОСТІЙНА РОБОТА В СИСТЕМІ ПІДГОТОВКИ КОНКУРЕНТОСПРОМОЖНОГО СПЕЦІАЛІСТА (Педагогіка вищої та середньої школи, 2006)
This article is devoted to the problem of organization of students’ independent work. The independent work is considered as the way of teachers training.